THREE-LEVEL INVERTER CONTROLLED BY MEANS OF HYSTERESIS CURRENT CONTROL. APPLICATION TO GRID INTEGRATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper describes the operational analysis results of a grid integration of distributed generation sources with an AC grid using multilevel inverter. The multilevel inverter is a three-level voltage source inverter (VSI), which is controlled by means of a novel vector hysteresis current control (V.H.C.C). The proposed V.H.C.C, which is based on error square areas, controls the three-phase load AC currents. The three load current errors are gathered into a single space vector quantity. In this case, the magnitude of the error vector is limited within boundary areas of a square shape. The control scheme is based on the detection of areas and sectors, in which the vector tip of the current error can be located. Then it applies an appropriate voltage vector among the 27 voltage vectors. Inherent advantages of current hysteresis controller are retained with the added advantage of adjacent voltage vector selection for hysteresis PWM control. Simple look-up tables are required for the detection of areas and sectors, and also for the vector selection. A detailed model of wind power generation, photo-voltaic generation and multilevel inverter with its current controlled SVPWM technique was implemented with a MATLAB.